Corruption Eradication in Indonesia during the Covid-19 Pandemic: An Analysis of the Implementation of Article 27 Law Number 2 of 2020 Concerning State Financial Policy and Financial System Stability for Handling Covid-19 Pandemic - Ginting, Jamin; Gabriella, Chelsya (International Journal of Criminology and Sociology, 2021)
As Indonesia announced its first Covid-19 case on 2 March 2020, the government issued Acts Number 2 Year 2020. Article 27.1 and 27.2 of the Act do not provide legal certainty because they may release the state-official-corruptors from their criminal responsibility. Through this paper, the author argues the criminal-responsibility exception by elaborating the ideas of the 1945 Constitution and the Corruption Act. The author uses normative legal research to construct the paper by bringing the 1945 Constitution, Indonesian Penal Code, and Government Administration Act as contra-materials toward Acts Number 2 Year 2020. The author also uses the theories from Indonesian Law Scholars to base the author’s argument. The paper provides the construction of criminal corruption as one of the essential parts of state loss. It also explains the solution to remove the criminal-responsibility-exception by using the excellent faith principle. The paper would return the good faith principle into the implementation of Act Number 2 Year 2020. As Act Number 2 Year 2020 is considerably new on implementation, this paper provides new insight into the better implementation of corruption-handling during the Covid-19 Pandemic.